The pendulum of participation: exploring shifting participation of Health Committees during the Covid-19 Pandemic in Cape Town sub-districts - Kannemeyer, Natasha (Department of Public Health and Family Medicine, 2023)
Community participation is a vital component of public health with meaningful participation centred around empowering communities, establishing trust and developing collaborations between community members, government, health professionals and other key stakeholders. Despite widespread acknowledgment of the importance of community participation, there are numerous barriers to meaningful participation. Power dynamics and the spaces where participation takes place impact both the level and quality of participation. This qualitative study explores how participation in health committee spaces was affected during the Covid-19 pandemic and how the relationship between the state and health committees evolved during the pandemic. Health committees are a form of institutionalised participation situated as part of primary health care clinics and consist of community representatives, clinic managers and municipal political representatives. A function of these committees is to bridge the gap between community members and health facilities. Focus group discussions were conducted with two health committees located in Gugulethu and Manenberg, two economically marginalised areas in Cape Town, South Africa. Participants in the study were comprised of health committee members. Transcripts were analysed using a thematic analysis approach. Initial data analysis was inductive. Two conceptual frameworks: Arnstein's Ladder of Participation and Gaventa's notion of invited and invented spaces were used to interpret the findings. The study found that pre-Covid, the relationship between health committees and the state was limited, with little collaboration. During the pandemic, health committees responded to community needs and filled gaps in the state's reach. Subsequently, the state recognised its limits and the need for collaboration with community actors to reach communities. This brought about an opening of previously closed spaces to include health committees in more meaningful forms of participation. However, like a pendulum swinging back and forth, participation closed back down. In this context, health committees challenged the ‘invited' space and invented their own spaces for participation. A number of challenges with invited participation were identified: lack of recognition, inadequate inclusion in state decisions, planning and implementation of interventions, lack of resources and state support and power dynamics. The study concludes that health committees occupy complex spaces and places of contestation where different actors continuously negotiate the dynamics of the space. Shifting participation requires a redistribution of power, the establishment of partnerships and trust and the creation of innovative, neutral spaces for collaboration.